Deciphering Interfacial Chemical and Electrochemical Reactions of Sulfide‐Based All‐Solid‐State Batteries. Issue 24 (6th May 2021) - Wang, Changhong; Hwang, Sooyeon; Jiang, Ming; Liang, Jianwen; Sun, Yipeng; Adair, Keegan; Zheng, Matthew; Mukherjee, Sankha; Li, Xiaona; Li, Ruying; Huang, Huan; Zhao, Shangqian; et al.
Abstract: Large interfacial resistance resulting from interfacial reactions is widely acknowledged as one of the main challenges in sulfide electrolytes (SEs)‐based all‐solid‐state lithium batteries (ASSLBs). However, the root cause of the large interfacial resistance between the SEs and typical layered oxide cathodes is not fully understood yet. Here, it is shown that interfacial oxygen loss from single‐crystal LiNi0.5 Mn0.3 Co0.2 O2 (SC‐NMC532) chemically oxidizes Li10 GeP2 S12, generating oxygen‐containing interfacial species. Meanwhile, the interfacial oxygen loss also induces a structural change of oxide cathodes (layered‐to‐rock salt). In addition, the high operation voltage can electrochemically oxidize SEs to form non‐oxygen species (e.g., polysulfides). These chemically and electrochemically oxidized species, together with the interfacial structural change, are responsible for the large interfacial resistance at the cathode interface. More importantly, the widely adopted interfacial coating strategy is effective in suppressing chemically oxidized oxygen‐containing species and mitigating the coincident interfacial structural change but is unable to prevent electrochemically induced non‐oxygen species. These findings provide a deeper insight into the large interfacial resistance between the typical SE and layered oxide cathodes, which may be of assistance for the rational interface design of SE‐based ASSLBs in the future. Abstract : Interfacial electrochemical and chemical reactions are analyzed in sulfide electrolyte (SE)‐based all‐solid‐state lithium batteries (ASSLBs). It is found that interfacial oxygen loss, coincident interfacial structural change, and electrochemical oxidation of SEs are responsible for the large interfacial resistance of SE‐based ASSLBs. The widely adopted interfacial coating is only effective in suppressing interfacial chemical reactions, but not electrochemical side reactions.